2019
DOI: 10.1177/1129729819862694
|View full text |Cite
|
Sign up to set email alerts
|

One- versus two-stage transposed brachiobasilic arteriovenous fistulae: A review of the current state of the art

Abstract: In the absence of suitable cephalic vein, the brachiobasilic vein complex represents the best option for arteriovenous access. However, the basilic vein is too deep to cannulate and requires transposition to be accessible. Transposition can be performed during fistula creation (single-stage BBTx) or at a second operation after initial fistula creation (two-stage brachiobasilic transposition (BBTx)). The best approach is unknown. A PubMed search using “Basilic vein transposition” as the primary search term was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…In this study, the early thrombosis rate was 18.8% [13]. In a meta-analysis by Sheta et al, primary patency rates for BVTAVF were found to be approximately 85% [14]. In the literature review, the primary patency rate of primary fistulas was found to be 75% to 90.3% [12][13][14].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In this study, the early thrombosis rate was 18.8% [13]. In a meta-analysis by Sheta et al, primary patency rates for BVTAVF were found to be approximately 85% [14]. In the literature review, the primary patency rate of primary fistulas was found to be 75% to 90.3% [12][13][14].…”
Section: Discussionmentioning
confidence: 52%
“…In a meta-analysis by Sheta et al, primary patency rates for BVTAVF were found to be approximately 85% [14]. In the literature review, the primary patency rate of primary fistulas was found to be 75% to 90.3% [12][13][14]. In our study, the percentages of primary patency rates at 3, 6, 9, 12, and 24 months were 96.6%, 93.1%, 92%, 87.4%, and 82.8% in BCAVF patients, and 96.7%, 93.3%, 90%, 86.7%, and 80% in BVTAVF patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In another meta-analysis by Sheta et al, 37 studies on one-stage versus two-stage BBAVF were evaluated. The one-year primary patency rates and incidence of complications were equivalent between the two procedures [ 19 ]. However, the secondary patency rate at one year was higher in the two-stage technique (79% versus 85%).…”
Section: Discussionmentioning
confidence: 99%
“…Authors emphasize that maturation, patency, failure and complication rates may suggest equivalence of both techniques. However, it is also emphasized that the strength of the evidence is limited [13,[15][16][17]. Some authors report that the one-stage technique decreases the time of maturation and the time to the first cannulation.…”
Section: One-stage Basilic Vein Tunneled Transposition For Hemodialysmentioning
confidence: 99%